2013
DOI: 10.1007/s11251-013-9266-5
|View full text |Cite
|
Sign up to set email alerts
|

Development of legal expertise

Abstract: In a comprehensive empirical investigation (N = 71,405) we analyzed the development of legal expertise in a critical 1-year period of academic legal training in which advanced law students start practicing to solve complex cases. We were particularly interested in the functional form of the learning curve and inter-individual differences in learning. Performance increases monotonically with the number of practice exams following a slightly concave learning curve without any considerable kinks. Considering the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Mock exams represent an additional stressor during exam preparation and this stress may have had such a strong impact on students at t2 that negative effects on well-being and recovery experiences were evident. This explanation relates to a study that found cyclic motivational drops as students progressed with their exam preparation [ 9 ]. Therefore, lower levels of motivation might also have affected the relationship between both physical activity and well-being as well as recovery experiences.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Mock exams represent an additional stressor during exam preparation and this stress may have had such a strong impact on students at t2 that negative effects on well-being and recovery experiences were evident. This explanation relates to a study that found cyclic motivational drops as students progressed with their exam preparation [ 9 ]. Therefore, lower levels of motivation might also have affected the relationship between both physical activity and well-being as well as recovery experiences.…”
Section: Discussionmentioning
confidence: 96%
“…The German system of legal education at university-level is a particular example of a state examination format that requires students to undergo a long preparation time to finish their formal studies and pass their first state examination [ 9 , 10 ]. Exam preparation takes about 18 months for most students and it is necessary to study an extensive amount of material and to take mock exams to practice solving legal cases.…”
Section: Introductionmentioning
confidence: 99%
“…The study of expertise is not new, however relatively few recent studies have examined the development of legal expertise. Glöckner et al (2013) highlight two potential reasons for this, including challenges in the effort and cost potentially required to recruit subjects with varying levels of legal expertise. They also highlight a challenge in finding a reliable outside criterion for performance in solving complex legal cases.…”
Section: Study 1 Literature Review Legal Expert-novice Comparative St...mentioning
confidence: 99%